The value of ultrasound grayscale ratio in the diagnosis of papillary thyroid microcarcinomas and benign micronodules in patients with Hashimoto’s thyroiditis: A two-center controlled study - Feng, Na; Wei, Peiying; Kong, Xiangkai; Xu, Jingjing; Yao, Jincao; Cheng, Fang; Ou, Di; Wang, Liping; Xu, Dong; Han, Zhijiang (Frontiers in Endocrinology, 2022)
Objective：The value of ultrasound gray scale ratio(UGSR)in the diagnosis of papillary thyroid microcarcinoma(PTMCs) and benign micronodules has been recognized by some authors, but those previous studies were not with Hashimoto's thyroiditis. This retrospective study investigated the value of ultrasound gray scale ratio in the diagnosis of papillary thyroid microcarcinoma and benign micronodules (BMNs) with Hashimoto's thyroiditis with data from 2 Medical Centers. Methods: This retrospective study used a total of 428 PTMCs with 368 HT cases and 225 BMNs with 181 HT cases from Medical Center A, paired comparing with a total 412 PTMCs with 324 HT cases and 315 BMNs with 229 HT cases from Medical Center B. All cases were surgically confirmed. UGSR was calculated as the ratio of the gray scale value of lesions to surrounding normal thyroid tissues. The optimal UGSR threshold of PTMCs and BMNs with HT from 2 Medical Centers was determined by Receiver operating characteristic curve (ROC). Statistics, including Aera under the curve(AUC), Optimal UGSR threshold，Sensitivity, Specificity and Diagnostic accuracy of the 2 Medical Centers，were paired analyzed in this study. Results: The UGSR of PTMCs and BMNs with HT from Medical Center A were0.5129 (0.4419, 0.5921) and0.8574 (0.6767, 0.9765) (Z=-15.564, P=0), and those from Medical Center B were0.514 (0.4306, 0.6254)and0.9165 (0.705, 1.1311) (Z=-15.564, P=0). As for the Medical Center A and B, The AUC, optimal UGSR threshold, Sensitivity, Specificity and Diagnostic accuracy of UGSR to differentiate PTMCs and BMNs with HT were 0.870 and 0.889, 0.68 and 0.70, 0.921 and 0.898, 0.747 and 0.759, and 0.861 and 0.836. There is no significant difference in UGSR between PTMCs of 2 Medical Centers (Z=-0.815, P=0.415), while there is significant difference in UGSR between BMNs of 2 Medical Centers (Z=-3.637, P=0). Conclusion: The UGSR to differentiate PTMCs and BMNs with HT has some reference value in improving TI-RADS according to its high Sensitivity and Diagnostic accuracy. However , due to its low Specificity, comprehensive analysis of other ultrasound signs is required.